Trigger happy or gun shy? : Dissolving common-value partnerships with Texas shootouts - Richard Brooks; Kathryn E. Spier (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
Many partnership contracts (and other joint-venture agreements) include so-called 'Texas Shootout Clauses' to govern future breakups. In a Texas Shootout, one partner names a single buy-sell price and the other partner has the option to buy or sell at that price. While the prior literature has considered the allocative efficiency of the Texas Shootout, this paper focuses on the incentives of private parties to make these offers to begin with. We consider a model where sole ownership is more efficient than joint ownership. Although both partners are equally capable, one has private information about the common value of the asset. When given the choice, they avoid making buy-sell offers because these offers give away bargaining surplus (the partners are "gun shy"). Instead, they often (but not always) prefer to make simple offers to buy or simple offers to sell and bargaining failures arise. Texas Shootout contracts that assign trigger rights - where one party can force the other to name a price - increase efficiency and are jointly desirable.
Keywords: 330; Personengesellschaft; Vertrag; Eigentümerstruktur; Ökonomischer Anreiz; Theorie